Risk for non-sentinel metastases in the contralateral groin in patients with a unilateral positive sentinel lymph node in primary vulvar cancer: a subgroup analysis of the AGO-VOP.2 QS Vulva Study - Jaeger, Anna; Hampl, Monika; Prieske, Katharina; Eulenburg, Christine Helene, Gräfin zu; Reichenbach, Juliane Renate; Klapdor, Rüdiger; Heublein, Sabine; Schochter, Fabienne; Gass, Paul; Rohner, Annika; Canzler, Ulrich; Becker, Sven; et al. (Gynecologic oncology, 2025)
The need for contralateral full groin dissection after bilateral sentinel node biopsy (SNB) with only unilateral detection of a macrometastasis is still a matter of debate. GROINSS-VI/II subanalysis has shown an absolute risk <3 % for contralateral groin recurrence or contralateral non-sentinel metastases, however, the individual risk varied widely dependent on the primary tumor characteristics. - Methods - The AGO VOP.2 QS vulva study is a retrospective, multicenter study. Data from 306 patients diagnosed with primary groin node positive VSCC (vulvar squamous cell carcinoma) between 2017 and 2019 at 33 gynecologic cancer centers in Germany were collected. In the current subgroup analysis, only patients with bilateral SNB and unilateral positive SNL were included. - Results - Of 306 documented groin node positive patients, 137 received bilateral SNB. Of these, 98 had a unilaterally positive SNL. The consecutive contralateral groin procedure was at the surgeons' discretion. 58/98 (59.2 %) received a bilateral inguinofemoral lymphadenectomy (if-LAE). 30/98 (30.6 %) underwent ipsilateral if-LAE only and 10/98 (10.2 %) had no further surgical treatment of the groins. 3/98 (3.1 %) patients either showed contralateral non-SN metastasis after bilateral if-LAE (n = 2) or developed isolated contralateral groin recurrence after unilateral if-LAE dissection (n = 1). - Conclusion - In this large multicenter retrospective study the risk of contralateral groin recurrence was low (3,1 %). Therefore, morbidity should be carefully balanced against oncologic safety and omission of contralateral LAE should be considered.
Online verfügbar: 16. Juli 2025, Artikelversion: 16. Juli 2025
Gesehen am 19.08.2025